2013
DOI: 10.5664/jcsm.3068
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of Patients with Obstructive Sleep Apnea in Korea

Abstract: Background: Obstructive sleep apnea (OSA) is associated with diverse health risks, including death. However, the role of OSA as a risk factor for death has never been studied in Asians. This study is aimed at evaluating the infl uence of OSA on the mortality in Korean sleep clinic population. Methods: A total of 2,240 patients who underwent in-laboratory full-night polysomnography due to snoring or sleep apnea were included. The patients were categorized based on apnea-hypopnea index (AHI)/hour. Death records … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 40 publications
2
21
0
1
Order By: Relevance
“…In a study reported by Lee et al, 8 it was found that the morbidity of OSA patients was directly related to its severity. Even though evidence based practices and AASM levels of recommendations advocate that occlusal changes are not always associated with the severity of OSA, extensive diagnostic protocols must be followed including occlusal discrepancies before initiating treatment with oral appliances in order to identify the ideal patient population with risk of complications and associated dental comorbidities.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a study reported by Lee et al, 8 it was found that the morbidity of OSA patients was directly related to its severity. Even though evidence based practices and AASM levels of recommendations advocate that occlusal changes are not always associated with the severity of OSA, extensive diagnostic protocols must be followed including occlusal discrepancies before initiating treatment with oral appliances in order to identify the ideal patient population with risk of complications and associated dental comorbidities.…”
Section: Discussionmentioning
confidence: 94%
“… 7 Patients suffering from OSA are also reported to have poor quality of sleep, daytime somnolence, cognitive disorders, hypertension, decreased productivity and increased incidence of vehicle accidents. 8 On the other hand obstructive sleep apnea syndrome (OSAS) is characterized by repetitive episodes of obstructive sleep apneas and hypopneas, which is frequently followed by transient desaturation of blood oxygen levels (hypoxemia) associated with arousal from sleep. 9 According to the American Academy of Sleep Medicine (AASM), the classification of OSA is based on the apnea-hypopnea index (AHI), which is defined by the average number of disordered breathing events per hour of sleep.…”
mentioning
confidence: 99%
“…Five studies explored the association of SDB and incident stroke in the general population [53][54][55][56]. Five studies evaluated prospectively [57][58][59] or retrospectively [60,61] the incidence of stroke or cardiovascular events in patients studied for suspected OSA. Three studies compared cardiovascular outcomes in patients with atrial fibrillation according to presence/absence of OSA [62][63][64].…”
Section: Results Of Literature Searchmentioning
confidence: 99%
“…A growing body of evidence has shown that (short or long) sleep duration [1,417], sleep disturbances [1,9,18] and obstructive sleep apnea (OSA) [1926] may predict all-cause [1,919,2125,2731], cardiovascular- [1,4,10,13,16,17,19,24,29], cancer- [1,16,17,24,30] and dementia-specific [6] mortality rates. Although there are distinct definitions for sleep duration, most studies examining short [1,6,911,16 ] or long sleep [5,11,13,15,32] as risk factors for all-cause or cause-specific mortality rates have considered 7–8 h as the optimal range for sleep duration [3336].…”
Section: Introductionmentioning
confidence: 99%